Language Learning and Literacy 2020
DOI: 10.4018/978-1-5225-9618-9.ch041
|View full text |Cite
|
Sign up to set email alerts
|

Cloud Applications in Language Teaching

Abstract: This study examined pre-service teachers' expertise, perceptions and integration of cloud applications in teaching of Arabic and English. Questionnaires and semi-structured interviews were used as data collection methods. The findings of the study specified that pre-service teachers did not own sufficient expertise for effective integration of cloud applications. The findings also revealed that participants perceived cloud applications as a valuable tool to improve many aspects of language education. Nonethele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…An analysis by Hermida et al (2022) found that more than half of 99 pre-service teachers regularly used cloud storage, the only media for which all methods of data protection were used. According to Aburezeq and Dweikat (2020), pre-service English teachers considered cloud applications favourably and integrated them successfully. Cloud computing facilitates planned collaboration, interpersonal interaction, and personalized learning (Çakiroglu& Erdemir, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…An analysis by Hermida et al (2022) found that more than half of 99 pre-service teachers regularly used cloud storage, the only media for which all methods of data protection were used. According to Aburezeq and Dweikat (2020), pre-service English teachers considered cloud applications favourably and integrated them successfully. Cloud computing facilitates planned collaboration, interpersonal interaction, and personalized learning (Çakiroglu& Erdemir, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%